The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1177/0278364909353640
|View full text |Cite
|
Sign up to set email alerts
|

Observability-based Rules for Designing Consistent EKF SLAM Estimators

Abstract: Abstract-In this work, we study the inconsistency problem of EKF-based SLAM from the perspective of observability. We analytically prove that when the Jacobians of the process and measurement models are evaluated at the latest state estimates during every time step, the linearized error-state system employed in the EKF has observable subspace of dimension higher than that of the actual, nonlinear, SLAM system. As a result, the covariance estimates of the EKF undergo reduction in directions of the state space w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
175
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 225 publications
(182 citation statements)
references
References 20 publications
5
175
0
2
Order By: Relevance
“…Due to linearization errors, the number of unobservable directions is reduced in a standard EKF-based VINS approach, allowing the estimator to gain spurious information and leading to inconsistency. What we present is a significant, nontrivial extension of our previous work on mitigating inconsistency in 2D robot localization problems [12]. This is due in part to the higher-dimensional state of the 3D VINS system as compared to 2D localization (15 elements vs. 3), as well as more complex motion and measurement models.…”
Section: Related Workmentioning
confidence: 86%
See 1 more Smart Citation
“…Due to linearization errors, the number of unobservable directions is reduced in a standard EKF-based VINS approach, allowing the estimator to gain spurious information and leading to inconsistency. What we present is a significant, nontrivial extension of our previous work on mitigating inconsistency in 2D robot localization problems [12]. This is due in part to the higher-dimensional state of the 3D VINS system as compared to 2D localization (15 elements vs. 3), as well as more complex motion and measurement models.…”
Section: Related Workmentioning
confidence: 86%
“…The work by Huang et al [11,12,13] was the first to identify this connection for several 2D localization problems (i.e., simultaneous localization and mapping, cooperative localization). The authors showed that, for these problems, a mismatch exists between the number of unobservable directions of the true nonlinear system and the linearized system used for estimation purposes.…”
Section: Related Workmentioning
confidence: 99%
“…However, to the best of our knowledge, prior to [15], no work has analytically examined the consistency of CL. In contrast, recent research has focused on the consistency of EKF-based simultaneous localization and mapping (SLAM) (see [24][25][26][27][28][29][30][31]), showing that the computed state estimates tend to be inconsistent. Specifically, Julier and Uhlmann [24] first observed that when a stationary robot measures the relative position of a new landmark multiple times, the estimated variance of the robot's orientation becomes smaller.…”
Section: Related Workmentioning
confidence: 99%
“…In our previous work [29][30][31], we conducted a theoretical analysis of the EKF-SLAM inconsistency, and identified as a fundamental cause the mismatch between the dimensions of the observable subspaces of the linearized system, employed by the EKF, and the underlying nonlinear system. Furthermore, we introduced the first estimates Jacobian (FEJ)-EKF and observability-constrained (OC)-EKF, which significantly outperform the standard EKF and the robocentric mapping algorithm [25], in terms of both accuracy and consistency.…”
Section: Related Workmentioning
confidence: 99%
“…11,12 This insight resulted in a number of observability-constrained EKF SLAM algorithms which significantly improve the SLAM consistency. 13 SLAM can also be formulated as a parameter estimation problem where all the robot poses from where the measurements were taken together with all the observed features are treated as a set of unknown constant parameters that need to be estimated. An objective function based on maximum likelihood of the parameter estimates can be formulated by using robot odometry measurements and robot-to-feature observation information to relate the unknown parameters.…”
Section: Introductionmentioning
confidence: 99%